Serum sickness-like reaction in a child associated with cefdinir - Loar, R.W.; Herman, A.C.; Lee, B.R.; Fischer, P.R. (European Journal of Pediatric Dermatology, 2012)
We report the case of a 22 month-old boy with diffuse erythematous plaques and papules with central clearing, fever, joint swelling, and polyarthralgia that presented seven days into a course of cefdinir for presumed pharyngitis. He was diagnosed with serum sickness-like reaction (SSLR) and had gradual improvement after discontinuation of cefdinir. This is the first reported case of cefdinir associated with SSLR.